Potential for use of Sargasum Mulch in Sweet Potato productionTT - Potentiel d'utilisation de Sargasse dans la production de patate douce - Veira, Andréa K. (University of the West Indies (Cave Hill, Barbados), 2016)
Practical uses of sargassum are sought at the regional level, as our coasts continue to be flooded by proliferations of sargassum floating ashore. This study examined the potential benefits of sargassum mulch in sweet potato production in Golden Ridge, St. George, Barbados, during a drought period (November 2015-March 2016). There seems to be some potential for the use of aged sargassum mulch to improve growth, pest control and sweet potato yields and other surveys are needed.